2016
DOI: 10.1155/2016/9848343
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Surface Effects on Thermomechanical Behavior of Embedded Circular Curved Nanosize Beams

Abstract: To investigate the surface effects on thermomechanical vibration and buckling of embedded circular curved nanosize beams, nonlocal elasticity model is used in combination with surface properties including surface elasticity, surface tension, and surface density for modeling the nanoscale effect. The governing equations are determined via the energy method. Analytically Navier method is utilized to solve the governing equations for simply supported nanobeam at both ends. Solving these equations enables us to es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 46 publications
(65 reference statements)
0
2
0
Order By: Relevance
“…Size-dependent theories including nonlocal, strain gradient and couple stress theories are better choices and present more accurate outputs in these cases [11,13,[49][50][51][52][53][54][55][56][57]. It should be noted that the mentioned theories consist of size-dependent parameters, in which their exact values must be determined by experimental data or numerical simulations [58][59][60][61]. Zhou et al [62] developed a new exact model based on Kirchhoff and surface elasticity theory for the investigation of vibra-tional behavior of the double-layer circular microplate.…”
Section: Introductionmentioning
confidence: 99%
“…Size-dependent theories including nonlocal, strain gradient and couple stress theories are better choices and present more accurate outputs in these cases [11,13,[49][50][51][52][53][54][55][56][57]. It should be noted that the mentioned theories consist of size-dependent parameters, in which their exact values must be determined by experimental data or numerical simulations [58][59][60][61]. Zhou et al [62] developed a new exact model based on Kirchhoff and surface elasticity theory for the investigation of vibra-tional behavior of the double-layer circular microplate.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is important to study the static, dynamic, and wave propagation behavior of structures made of FG materials. [4][5][6][7][8][9][10][11][12][13][14] Wave propagation of porous FG plates employing various higher-order shear deformation theories is investigated by Yahia et al 15 They concluded that higher order theories can accurately predict the wave characteristics of FG structures and only a little difference exists between their results. Also, many articles are published concerning with analysis of FGM structures based on higher order shear deformation theories.…”
Section: Introductionmentioning
confidence: 99%